Fintech investments in European banks: A hybrid IT2 fuzzy multidimensional decision-making approach - Gang Kou; Özlem Olgu Akdeniz; Hasan Dinçer; Serhat Yüksel (Financial Innovation, 2021)
Financial technology (Fintech) makes a significant contribution to the financial system by reducing costs, providing higher quality services and increasing customer satisfaction. Hence, new studies play an essential role to improve Fintech investments. This study evaluates Fintech-based investments of European banking services with an application of an original methodology that considers interval type-2 (IT2) fuzzy decision-making trial and evaluation laboratory and IT2 fuzzy TOPSIS models. Empirical findings are controlled for consistency by applying the VIKOR method. Moreover, we conduct a sensitivity analysis by considering six distinct cases. This study contributes to the existing literature by identifying the most important Fintech-based investment alternatives to improve the financial performance of European banks. Our empirical findings illustrate that results are coherent, reliable, and identify "competitive advantage" as the most important factor among Fintech-based determinants. Moreover, "payment and money transferring systems" are the most important Fintech-based investment alternatives. It is recommended that, among Fintech-based investments, European banks should mainly focus on payment and money transferring alternatives to attract the attention of customers and satisfy their expectations. This is also believed to have a positive impact on the ease of bank' receivable collection. Another important point is that Fintech-based investments in money transferring systems could help to decrease costs.
Keywords: 650; DEMATEL; European banking industry; Financial technology; Interval type-2 fuzzy TOPSIS